2014
DOI: 10.3389/fendo.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Protein Synthesis and Actin Polymerization in Hippocampal Neurons through Different Molecular Mechanisms

Abstract: Estrogen rapidly modulates hippocampal synaptic plasticity by activating selective membrane-associated receptors. Reorganization of the actin cytoskeleton and stimulation of mammalian target of rapamycin (mTOR)-mediated protein synthesis are two major events required for the consolidation of hippocampal long-term potentiation and memory. Estradiol regulates synaptic plasticity by interacting with both processes, but the underlying molecular mechanisms are not yet fully understood. Here, we used acute rat hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 61 publications
5
54
0
Order By: Relevance
“…We also found that estrogen stimulates the same signaling cascade in hippocampal slices via activation of GPER1 (Briz and Baudry, 2014). Here, we report that E 2 -and G1-induced increase in Akt/mTOR signaling and protein translation requires BDNF release and TrkB receptor activation.…”
Section: Roles Of Gper1 and Bdnf In Mossy Fiber Synaptic Plasticitysupporting
confidence: 56%
See 1 more Smart Citation
“…We also found that estrogen stimulates the same signaling cascade in hippocampal slices via activation of GPER1 (Briz and Baudry, 2014). Here, we report that E 2 -and G1-induced increase in Akt/mTOR signaling and protein translation requires BDNF release and TrkB receptor activation.…”
Section: Roles Of Gper1 and Bdnf In Mossy Fiber Synaptic Plasticitysupporting
confidence: 56%
“…While the subcellular localization of GPER1 has remained controversial (Srivastava and Evans, 2013), recent ultrastructural analyses have identified GPER1 in hippocampal dendritic spines and axon terminals (Akama et al, 2013;Waters et al, 2015), which suggests its involvement in synaptic plasticity. In this regard, we recently reported that E 2 -induced activation of the mechanistic target of rapamycin (mTOR) in hippocampal neurons is mediated by GPER1 (Briz and Baudry, 2014), an event required for estrogen regulation of memory consolidation (Fortress et al, 2013). Yet, the role of GPER1 activation in hippocampal synaptic plasticity is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, E 2 increases the probability of glutamate release (Smejkalova and Woolley, 2010) and increases the NR2B component of excitatory synaptic currents (Snyder et al, 2011). Recent studies show that E 2 also acts to promote actin polymerization within dendritic spines, which optimizes synaptic physiology (Kramar et al, 2013; Briz and Baudry, 2014). E 2 activates a signaling cascade involving GTPase RhoA within the spine and inactivates the filament severing protein cofilin (Kramar et al, 2013), which would promote spine stability.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of these non-genomic transduction pathways, both sex hormones can activate multiple signalling pathways, including cAMP/protein kinase A (PKA), mammalian target of rapamycin (mTOR), mitogen-activated protein kinase/extracellular signal-regulated kinases (MAPK/ERK) and protein kinase B (Akt/PKB), that are involved in synaptic plasticity and neuroprotection [38,39]. As this is a new field of research, a recent finding that estradiol-elicited mTOR activation in the hippocampus was blocked by a very specific antagonist of GRP-30 and not by the antagonists of classical ERα/β, puts a totally different light on this type of receptor in the context of cognition [39].…”
Section: Non-genomic Effectsmentioning
confidence: 99%
“…The WHIMS study used MPA, which could explain why HT worsened the cognition in postmenopausal women (Table 4) [11,15,16]. Formulations that contain a combination of CEE and MPA are commonly prescribed clinically for the relief of hot flashes and related symptoms [16,51], but the effect of treatment on cognitive function in postmenopausal women remains controversial [10,39]. So, both in preclinical and clinical trials it is important to test different combinations of hormones.…”
Section: Type (Composition) Of Htmentioning
confidence: 99%